ETHICAL DILEMMA AND LEGAL RESPON ETHICAL DILEMMA AND LEGAL RESPONSIBILITIES OF HEALTH PERSONNEL IN HIV AIDS SERVICES AT PUSKESMAS SENTANI: ETHICAL DILEMMA AND LEGAL RESPONNSIBILITIES OF HEALTH - makualaina, fenska (STIKES Bethesda Yakkum, 2024)
ABSTRACT Background: The increasing incidence of HIV AIDS in Papua hopes for changes by paying attention to all aspects of health services provided to patients with HIV AIDS, one of which is the role and responsibility of health workers in providing preventive, promotive, curative and rehabilitative services. Method: Design used was descriptive qualitative with a Phenomenology approach. This research was carried out at the Sentani Community Health Center VCT Polyclinic with three health workers participating. Objective: Describe the ethical dilemmas and legal responsibilities of health workers in caring for patients with HIV AIDS. Results: It was found that there were five themes from the results of the research conducted, including forms of ethical dilemmas, the role of health workers, obstacles in providing services to HIV AIDS patients, legal responsibility, and legal protection. Conclusion: In this study, health workers were faced with two alternative choices where there was no satisfactory solution to the problem, so this situation became a consideration for health workers in making a decision in providing services. This ethical dilemma certainly carries the risk of giving rise to legal responsibility and legal protection for health workers. Key words: Ethical dilemma, legal responsibility, health workers